ANALYSIS OF RESTAURANT TAX ON ORIGINAL REGIONAL INCOME REVENUE IN MEDAN CITY - Angelia, Nina; Sihombing, Marlon; Kusmanto, Heri; Ridho, Hatta (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The purpose of this research is to analyze the establishment of restaurant tax on receipts of local real income in the City of Medan. This type of research is qualitative research. Data collection techniques are carried out through interviews, observations, library studies, documentation and focus group discussions. The results of this study found that the reception of local income as a restaurant tax in the City of Medan is still not optimal. The impact of restaurant tax on development is as a source of regional financing in the maintenance of regional development, thus will improve and regulate the economy as well as the well-being of the people. The strategy to increase the income of the region is restaurant tax support of public participation to build public confidence in the quality of tax services fair, accountable, transparent